Population‐based study of the prevalence and management of self‐reported high pain scores in patients with non‐resected pancreatic adenocarcinoma. Issue 12 (22nd October 2019) - Tung, S.; Coburn, N. G.; Davis, L. E.; Mahar, A. L.; Myrehaug, S.; Zhao, H.; Earle, C. C.; Nathens, A.; Hallet, J.
Abstract : Background: Pain is a common debilitating symptom in pancreatic adenocarcinoma. This cohort study examined the use of, and factors associated with, pain‐directed interventions for a high pain score in patients with non‐curable pancreatic adenocarcinoma. Methods: Administrative databases were linked and patients with non‐resected pancreatic adenocarcinoma diagnosed between 2010 and 2016, who reported one or more Edmonton Symptom Assessment System (ESAS) score, were identified. A high pain score was defined as an ESAS score of at least 4. Outcomes were pain‐directed interventions: opiates (in patients aged 65 years or more with universal drug coverage), nerve block and radiation therapy for a high pain score. Reduction in pain score of at least 1 point after pain‐directed intervention was also evaluated. Modified Poisson regression was used to examine factors associated with pain‐directed intervention. Results: Among 2623 patients with a median age of 67 years, 1223 (46·6 per cent) were women, and 1621 (61·8 per cent) reported a high pain score at a median of 38 days after diagnosis. Of those with a high pain score, 75·6 per cent (688 of 910) received opiates, 13·5 per cent (219 of 1621) radiation and 1·2 per cent (19 of 1621) nerve block. The pain score decreased in 62·1 per cent of patients after administration of opiates, 73·4 per cent after radiation and all patients after nerve block. In multivariable analysis, no patient factor (age, sex, co‐morbidity burden, rurality, income quintile) was associated with receipt of non‐opiate pain‐directed intervention for a high pain score. In patients aged at least 65 years, advanced age was associated with lower odds of opiate use. Conclusion: Opiates are the most common pain‐directed intervention for non‐curable pancreatic adenocarcinoma, whereas radiation therapy and nerve blocks are seldom used. The lack of association between pain‐directed interventions and patient factors points toward practice‐driven patterns. Abstract : Patient‐reported outcomes were linked to healthcare databases to examine patterns of care for patients with non‐curative pancreatic adenocarcinoma reporting high pain scores. Opiates are currently the most commonly used pain‐directed intervention, whereas non‐opiate strategies such as radiation and nerve blocks are potentially underused, despite being effective in reducing pain scores. ESAS, Edmonton Symptom Assessment System. Pain management an issue Abstract : Antecedentes: El dolor es un síntoma debilitante frecuente en el adenocarcinoma de páncreas. Este estudio de cohortes examinó el uso de las intervenciones dirigidas para el tratamiento del dolor y los factores asociados a las mismas en pacientes con adenocarcinoma pancreático incurable que presentaban puntuaciones altas de dolor. Métodos: Se revisaron las bases de datos administrativas y se identificaron los pacientes con adenocarcinoma pancreático no resecado diagnosticados entre 2010‐2016 con puntuaciones > 1 del Sistema de Evaluación de Síntomas de Edmonton ( Edmonton Symptom Assessment System, ESAS). La puntuación alta de dolor se definió como ESAS > 4. Los resultados evaluados fueron las intervenciones dirigidas contra el dolor: opiáceos (en pacientes mayores de 65 años con cobertura universal de medicamentos), bloqueo nervioso y radioterapia en el caso de puntuación alta del dolor. También se evaluó la reducción en la puntuación del dolor (> 1 punto) después de la intervención dirigida contra el dolor. Los factores asociados a la intervención contra el dolor se analizaron mediante una regresión de Poisson modificada. Resultados: De los 2.623 pacientes con una mediana de edad de 67 años, 1.223 (46, 6%) eran mujeres, y 1.621 (61.8%) presentaron una puntuación alta de dolor con una mediana de 38 días desde el momento del diagnóstico. De aquellos con puntuación alta de dolor, el 75, 6% recibió opiáceos ( n = 688/910), el 13, 5% radiación ( n = 219/1.621) y el 1, 2% bloqueo nervioso ( n = 19/1.621). La puntuación del dolor disminuyó en el 62, 2% después del tratamiento con los opiáceos, en el 73, 8% después de la radiación y en el 100% después del bloqueo nervioso. En el análisis multivariable, ningún factor relacionado con el paciente (edad, sexo, comorbilidades, vivir en una zona rural, quintil de ingresos) se asoció con una intervención dirigida contra dolor sin opiáceos en los casos de puntuación alta del dolor. En pacientes mayores de 65 años, la edad avanzada se asoció con menor probabilidad de uso de opiáceos. Conclusión: Mientras que los opiáceos son la intervención dirigida contra dolor más común para el adenocarcinoma pancreático no resecable, la radioterapia y el bloqueo nervioso rara vez se usan. La falta de asociación de las intervenciones dirigidas contra el dolor con los factores del paciente apunta hacia el uso de patrones terapéuticos basados ​​en la práctica clínica.